DEVELOPMENT OF A LOCAL WISDOM-BASED MARINE GOVERNANCE CONTROL MODEL FOR OPTIMIZING ANIMAL PROTEIN PROCESSING IN THE PREVENTION OF STUNTING IN KUPANG CITY - Hendrikus Likusina Kaha; Indriyati Indriyati; Yosef Pandai Lolan (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2026)
Indonesia as an archipelagic country has great potential in providing marine resources rich in animal protein. Indonesian seas are estimated to contain around 60% of the world's total fish resources, making it one of the natural resources with great potential in providing nutritious food. Animal protein has an important role in preventing or minimizing the occurrence of stunting in toddlers. This study aims to develop a marine governance control model based on local wisdom, which can optimize the processing of animal protein from marine resources to support stunting prevention. In this study, the researchers used a Research and Development (R&D) research type with an Instructional Design Development design, including the approach, the design used was ADDIE (Analysis, Design, Development, Implementation, Evaluation). Based on the results of the Wilcoxon Signed Ranks Test on 15 statements, all indicators showed a significance value of p <0.05 (even most p = 0.000), which means there was a significant difference between the conditions before and after the application of the model. The analysis results indicate that this model is effective in increasing awareness, knowledge, and practices of animal protein processing and consumption relevant to the local context.